Asthma Knowledge and Behaviours among Parents of Asthmatic Children Attending Paediatric Hospitals in Mosul City (Medico Legal Update, 2020)
Background: Asthma is a common health problem among all age groups. It disturbs all aspects of children’slife and possibly changes to chronic disease that continues for the whole patient’s life. This research focusedattention on the parental knowledge and practices during and between asthmatic attacks in order to identifyimproper activities and improve their future performance toward their children.Objective: This research aims to demonstrate the degree of parental knowledge and behaviours toward theirchildren during and between asthmatic attacks in Mosul City.Method: A case series study was conducted among 312 parents of asthmatic children that attended Al-Khansaaand Ibn-Alatheer teaching hospitals (two major paediatric hospitals in Mosul City)over a period of 6 months.A questionnaire form derived from “the Arabic version of the Chicago Community Asthma SurveyQuestionnaire” was distributed among the participants to evaluate their demographic characteristics, myths,knowledge, and behaviours. Various rates and proportions are used to explain these variables.Results: This study shows that most parents got information from doctors (62.2%), their best knowledgewas about the precipitating factor for asthma as dust and smoke (78%) and the symptoms of asthma asdyspnoea (84.9%), while the least information were about the mechanism of disease where 26.9% did notknow the exact mechanism, and the complications of asthma as sudden death (25.3%). On the other hand,the best parental behaviour was the regular use of medications during and between attacks (88.5% and82.7%) and the lowest ones was performing breathing exercises (around 45%).Conclusion and Recommendation: A relatively adequate knowledge and behaviours were documented inthis study; however, further education about the recent guidelines for asthma management should be offeredto those parents in order to improve their offspring health and lifestyle.